Challenges of Parenting in the Digital Era: A Review from the Perspective of Islamic Family Law - Bukhari, Bukhari; Bastiar, Bastiar; Anwar, Anwar (Hukum Keluarga Islam IAIN LANGSA, 2024)
This study examines the challenges of child-rearing within Muslim families in the digital era, focusing specifically on the perspective of Islamic family law. The research addresses Muslim parents' complex issues in adapting Islamic family law principles to parenting practices compatible with digital realities. The study aims to identify significant challenges encountered in digital parenting and to propose relevant legal recommendations to support Muslim families. Using a qualitative approach with data collection techniques such as in-depth interviews, observations, and focus group discussions, the study involved 30 Muslim families, Islamic scholars, and legal experts. The findings reveal that critical challenges include difficulties in the digital supervision of children, low digital literacy among parents, and value conflicts between Islam and digital culture. The study highlights the need for supportive legal adaptations that preserve Islamic character education within the digital context, helping safeguard children's ethics and morals. Effective strategies include balanced surveillance technology aligning with Islamic values and implementing digital use guidelines. The study's implications emphasize the importance of collaboration among legal experts, policymakers, and stakeholders to establish a responsive legal framework addressing digital challenges and supporting Muslim families in integrating child-rearing with religious teachings.